Volumetric properties of binary mixtures of methanol with ethyl caprylate, ethyl caprate, and ethyl laurate from 283.15 to 318.15 K. (October 2018) - Xia, Juan; Di, Gaolei; Sun, Yanjun; Wang, Xiaopo; Yang, Xiaohu; He, Siyuan
Abstract: Density and viscosity for mixtures of alkyl esters with alcohols is essential not only for simulation and optimization of diesel engine but also for the understanding of the interactions between them. The new densities of binary mixtures of methanol with three fatty acid ethyl esters (ethyl caprylate, ethyl caprate, and ethyl laurate) were measured at the atmospheric pressure for the temperatures ranging from (283.15 to 318.15) K over the entire composition range using an Anton Paar digital vibrating U-tube densimeter (model DMA 5000 M). A Redlich–Kister type equation was correlated using the excess molar volumes calculated with the experimental values and used to represent the densities of the liquid mixtures as a function of temperature and concentration.